Balanced scorecard analysis to measure the performance of PT. KAI Jombang City - Lailatus Sa'adah; Nur Fauziyah (Institute of Computer Science (IOCS), 2023)
Performance determination is the main objective of this study. PT. KAI Jombang City using a financial perspective, internal company perspective, learning and growth perspective are the four perspectives of the balanced scorecard. Type This research uses quantitative methods and is descriptive in nature. tools for collecting data which includes surveys, interviews, and documentation. Respondents on customer satisfaction are customers of PT. KAI Jombang City totaled 100 people while respondents to employee satisfaction were employees of PT. KAI Jombang City numbered 30 people. The sampling technique uses a probability sample. The results of this study The results of this study from a financial perspective, namely the economic ratios decreased by 42.6%. Efficiency has decreased by 36.1%. Effectiveness decreased by 0.1%. Customer satisfaction trust value shows the highest value of 89%. In the internal business, new innovations such as the addition of VIP rooms, AC standing, display screens, parking areas for box counters and reductions. In the operation process using GAPEKA (Rail Travel Graph). In the after-sales process of giving points and rewards. Meanwhile, from the perspective of growth and learning, the indicator of satisfaction with supervision and salary results has the highest value, namely 90%. On retention only 10% of employees leave, meaning good performance. Productivity has decreased by Rp. 22,695.43, meaning that performance is said to be lacking